DEIXIS IN JULIAN TREASURE’S TEDTALKS : “HOW TO SPEAK SO THAT PEOPLE WANT TO LISTEN” - Sihombing, Meyta Isenda P.; Silalahi, Charles David Marudut (Cahaya Ilmu Bangsa Institute, 2025)
This research analyzes Julian Treasure's use of deixis in his TED Talk,